ANALYSIS OF THE LAW OF THE REPUBLIC OF KAZAKHSTAN «ON RAILWAY TRANSPORT» AND THE PRACTICE OF ITS APPLICATION - Rakisheva Алуа Курмангалиевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
In September, 2018 the staff of the Center of legal monitoring of GU «Institute of the Legislation of the Republic of Kazakhstan» carried out legal monitoring of the Law of the Republic of Kazakhstan “On Railway Transport”. The article provides an analysis of the problematic issues of this Law on the basis of studying the practice of its application and addresses the problems of improving the quality of services for the transport of passengers by rail. As a result of legal monitoring of the Law of the Republic of Kazakhstan «On Railway Transport» identified problems in terms of the conceptual apparatus. It is necessary to introduce new terms into the Law that will fully reflect the peculiarities of legal regulation of the use of railway transport. The Law does not provide for liability rules for inappropriate maintenance of railway stations, which is a gap in legal regulation and therefore it is necessary to revise the provisions of the Law in order to supplement the rules on liability of persons owning or otherwise. The analyzed Law does not set forth requirements for the quality of services provided in trains, including the provision of a set of bedding of proper type and safe for use. It is necessary to envisage in the Law provisions regulating the issues of high-speed railways, as today one of the important factors restraining the successful participation of Kazakhstan in international transportation is the lack of high-speed railways, which does not allow Kazakhstan’s railway transport to reach a new level of development. It is also advisable to introduce administrative responsibility of passengers for ticketless travel and redemption of tickets and introducing legislation on mandatory SMS-notification of passengers in cases of changes in train schedules or their delays, as well as the electronic queue system when buying train tickets. The results of the study can be used in legislative work to improve the legislation of the Republic of Kazakhstan regulating the sphere of railway transport, as well as in scientific research in this area.